A wrinkled structure of gold film greatly improves the signaling of electrochemical aptamer-based biosensors. Issue 2 (6th January 2021) - Li, Shaoguang; Lin, Lancy; Chang, Xueman; Si, Zhixiao; Plaxco, Kevin W.; Khine, Michelle; Li, Hui; Xia, Fan
Abstract : A wrinkled gold substrate greatly improves the signaling of electrochemical aptamer-based biosensors, achieving up to 10-fold increase in signals. Abstract : Electrochemical aptamer-based (E-AB) sensors provide a great opportunity towards the goal of point-of-care and wearable sensing technologies due to their good sensitivity and selectivity. Nevertheless, the output signals from this sensor class remain low when sensors are interrogated via square-wave voltammetry. This low signaling limits the sensor's precision for its capability to detect small changes in target concentrations. To circumvent this, we proposed here the use of a readily shrink-induced, wrinkled Au-coating polyolefin film to immobilize a greater number of DNA probes and thus improve the signaling. Specifically, wrinkled gold film exhibits a 5.5-fold increase of surface area in comparison to the unwrinkled ones. Using these substrates we fabricated a set of E-AB sensors of three biological molecules, including kanamycin, doxorubicin and ATP. We achieved up to 10-fold increase in its current and also good accuracies within ±20% error in the target concentration range across 2 orders of magnitude.